We must not be enemies restoring America's civic tradition - Austin, Michael, 1966- (Rowman & Littlefield, 2019)
Democracy requires citizens who can argue as friends. Disagreement drives our democratic processes, but outrage and enmity degrade the civic fabric that enables us to govern ourselves. We Must Not Be Enemies explores the American tradition of civic debate and argues that the health of our democracy requires that we work to recover this tradition.